2012
DOI: 10.5301/hip.2012.9751
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing Reproducibility for Radiographic Measurement of Leg Length Inequality after Total Hip Replacement

Abstract: Leg length inequality (LLI) following total hip replacement (THR) can cause considerable morbidity Although it was described when the technique was popularized in the 1960s, it remains a significant challenge to arthroplasty surgeons .This study reviews the established practice for the measurement of LLI on plain AP radiograph, and compares these techniques to two methods used locally. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…In the Woolson method, the inter teardrop-lesser trochanter distance is used, while in the Willamson method, the transischial line-lesser trochanter distance is used. Other bony landmarks used include center of rotation of femoral head-lesser trochanter (CFR-LT method) and center of rotation of femoral head-teardrop-lesser trochanter (CFR-T-LT) (16). These methods have been validated in the literature (16,23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Woolson method, the inter teardrop-lesser trochanter distance is used, while in the Willamson method, the transischial line-lesser trochanter distance is used. Other bony landmarks used include center of rotation of femoral head-lesser trochanter (CFR-LT method) and center of rotation of femoral head-teardrop-lesser trochanter (CFR-T-LT) (16). These methods have been validated in the literature (16,23).…”
Section: Discussionmentioning
confidence: 99%
“…This was done using the method described by McWilliams et al. (16). The stem length at the operated side was measured as the distance between the lesser trochanter and teardrop and the cup length as the distance between the teardrop and the center of rotation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Any further surgical interventions or complications were recorded. On the pre and post operative X-ray, the leg length was measured to the nearest mm, using Woolson's validated X-ray technique which references the centre of femoral rotation, the acetabular teardrop and the midpoint of the lesser trochanter, 14,15 (Figure 4).…”
Section: Methodsmentioning
confidence: 99%
“…The authors have found the Leeds method to be similarly accurate for the measurement of LLI but with better repeatability than the two prominent methods in the literature (Figure 6). 20 The authors recommend that a lateral hip radiograph should also be obtained to check for any atypical bony anatomy in the hip or femoral shaft.…”
Section: Investigationsmentioning
confidence: 99%